(untitled) (International Journal of Economics Management and Social Science, 2026)
This study aims to examine the transformation of marketing and services in the implementation of Umrah pilgrimage at PT Nur Haramain Mulia. The background of this study is based on the increasing public demand for professional, transparent, and digital-based Umrah services, as well as the challenges of industry competition and changes in government regulations. The research method used is qualitative with a field study approach. Data collection was conducted through in-depth interviews with pilgrims and company staff, observation of the service process, and analysis of supporting documents. The results of the study show that the marketing transformation at PT Nur Haramain Mulia was carried out through the integration of conventional and digital strategies, including the use of social media, official websites, testimonial content, and partnerships with various religious institutions. In terms of services, the company implements integrated services ranging from administration, rituals, assistance, to accommodation facilities that are oriented towards the comfort of pilgrims. Although digital innovation has been running well, its effectiveness is still influenced by the digital literacy of pilgrims, the level of competition, and limited marketing resources. This study concludes that the success of umrah marketing and service transformation is largely determined by the synergy between service professionalism, targeted digital innovation, and the continuous building of pilgrim trust